Penerapan Tranformasi Digital dan Hambatannya Pada Industri Kuliner di Indonesia - Wimber Jerry Panjaitan; Feri Lupiana (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
In this era of digitalization, business actors trying to adapt and be creative with a digital approach is a necessity. The ability of organizations to continue to survive is determined by their ability to adapt to technological advances in industry 4.0. In previous studies, many have investigated the opportunities presented by the role of digital transformation, but there are still obstacles and challenges faced in implementing this digital transformation. The culinary industry, which focuses on customer service and convenience in the process of implementing digital transformation in its business, also faces challenges in its journey. This study aims to discuss and identify obstacles and challenges faced by culinary industry players in the form of restaurants that are transitioning to implementing digital transformation in their services. Qualitative research methods were used in this study by conducting semi-structured interviews with owners, managers and employees in the culinary industry in several cities in Indonesia. Data collection based on empirical reviews and theoretical theories: lack of knowledge, lack of resources and cultural change. Empirical findings in the study show that most restaurants that are implementing digital transformation face challenges in terms of lack of resources, cultural change and lack of knowledge. The implications of this research can provide an overview for practitioners regarding the obstacles and challenges that restaurants will face in the process of implementing digital transformation in their business. This research can also be used as literature to fill the gaps that exist in the obstacles and challenges of digital transformation, especially in business.